The use of high-dose melatonin in liver resection is safe: first clinical experience - Nickkholgh, Arash; Schneider, Heinz; Sobirey, Michael; Venetz, Werner P.; Hinz, Ulf; Pelzl, Le H.; Gotthardt, Daniel; Cekauskas, Albertas; Manikas, Martynas; Mikalauskas, Saulius; Mikalauskene, Laura; Bruns, Helge; et al. (Journal of pineal research, 2011)
Abstract: Experimental data suggest that melatonin decreases inflammatory changes after major liver resection, thus positively influencing the postoperative course. To assess the safety of a preoperative single dose of melatonin in patients undergoing major liver resection, a randomized controlled double-blind pilot clinical trial with two parallel study arms was designed at the Department of General and Transplantation Surgery, Ruprecht-Karls-University, Heidelberg. A total of 307 patients, who were referred for liver surgery, were screened. One hundred and thirteen patients, for whom a major liver resection (≥3 segments) was scheduled, were eligible. Sixty-three eligible patients refused to participate, and therefore, 50 patients were randomized. A preoperative single dose of melatonin (50 mg/kg BW) dissolved in 250 mL of milk was administered through the gastric tube after the intubation for general anesthesia. Controls were given the same amount of microcrystalline cellulose. Primary endpoint was safety. Secondary endpoints were postoperative complications. Melatonin was effectively absorbed with serum concentrations of 1142.8 ± 7.2 ng/mL (mean ± S.E.M.) versus 0.3 ± 7.8 ng/mL in controls (P < 0.0001). Melatonin treatment resulted in lower postoperative transaminases over the study period (P = 0.6). There was no serious adverse event in patients after melatonin treatment. A total of three infectious complications occurred in either group. A total of eight noninfectious complications occurred in five control patients, whereas three noninfectious complications occurred in three patients receiving preoperative melatonin (P = 0.3). There was a trend toward shorter ICU stay and total hospital stay after melatonin treatment. Therefore, a single preoperative enteral dose of melatonin is effectively absorbed and is safe and well tolerated in patients undergoing major liver surgery.
Gesehen am 22.09.2022